Socioeconomic stratification in adolescent digital engagement: cultural capital, emotional mediation, and bilibili usage patterns in Chinese high schools - Liu, Qiaoyi (Frontiers in Sociology, 2026)
This sociological study examines how cultural capital and institutional structures shape digital behaviors among 606 Chinese high school students using stratified sampling across school types (provincial/municipal/regular) and income groups. Applying Bourdieu's capital theory within an Affect-Behavior-Cognition framework, we reveal entrenched stratification: students from high-income households (≥310,000 CNY) demonstrate significantly stronger cultural identity (ΔM = 0.15, F = 2.533, p = 0.048) and social interaction (ΔM = 0.24, F = 3.767, p = 0.005) compared to low-income peers, while municipal key school students exhibit 12% higher social interaction engagement than regular school counterparts (F = 2.694, p = 0.031). Parental occupation further mediates cultural capital conversion, with executives' children showing higher cultural identity (ΔM = 0.23 vs. service workers, p = 0.018). Crucially, emotion (β = 0.939, p < 0.001) serves as the mechanism that translates cognitive resources (entertainment β = 0.210, resources β = 0.210) into behavioral capital, yet this mediation pathway is disproportionately accessible to economically advantaged youth. Residential location showed no significant effects, indicating Bilibili's uniform penetration but stratified usage patterns. These findings demonstrate how educational systems and familial capital jointly reproduce digital inequalities, with emotion serving as an overlooked conduit for converting cognitive advantages into behavioral capital. The study advances Bourdieusian theory in platform societies and proposes interventions for democratizing digital habitus through equitable content algorithms and school-based digital literacy programs.